Low Level of Dietary Organic Trace Minerals Improved Egg Quality and Modulated the Status of Eggshell Gland and Intestinal Microflora of Laying Hens During the Late Production Stage - Dong, Yuanyang; Zhang, Keke; Han, Miaomiao; Miao, Zhiqiang; Liu, Ci; Li, Jianhui (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the effects of dietary organic trace minerals on egg quality and intestinal microflora of laying hens during the late production stage. In total, 1,080 Jinghong-1 laying hens aged 57 weeks were randomly assigned to five treatment groups: CON, basal diet containing about 6, 29, 49, and 308 mg·kg−1 of Cu, Mn, Zn, and Fe; IT100, basal diet supplemented with 10, 80, 80, and 60 mg·kg−1 of Cu, Mn, Zn, and Fe (each as inorganic sulfates), respectively; OT20, basal diet supplemented with 2, 16, 16, and 12 mg·kg−1 of Cu, Mn, Zn, and Fe (each as organic trace minerals chelated with lysine and methionine in the ratio of 2:1 amino acid: organic trace minerals), respectively; OT30, basal diet supplemented with 3, 24, 24, and 18 mg·kg−1 of organic Cu, Mn, Zn, and Fe, respectively; and OT50, basal diet supplemented with 5, 40, 40, and 30 mg·kg−1 of organic Cu, Mn, Zn, and Fe, respectively. Overall, OT20, OT30, and OT50 had equal or higher potential to promote Cu, Mn, Zn, and Fe deposition in egg yolks compared with IT100. In addition, OT50 enhanced the eggshell breaking strength and the antioxidant status of the eggshell gland. Cecal microbiota, including Barnesiellaceae and Clostridia, were significantly decreased in IT100- and OT50-treated hens compared with the CON group. Clostridia UCG-014 was negatively correlated with eggshell weight and OCX-32. In conclusion, reduced supplementation of organic trace minerals can improve the eggshell quality and trace mineral deposition, possibly by modulating genes involved in the eggshell formation in the eggshell gland and by controling of the potentially harmful bacteria Barnesiellaceae and Clostridiales in the cecum. Inorganic trace minerals may be effectively replaced by low level of complex organic trace minerals in laying hens during the late production stage.